Escape mortality of cod, sithe and haddock in a Barents Sea trawl fishery - Ingólfsson, Ólafur Arnar; Soldal, Aud Vold; Huse, Irene; Breen, Mike (Elsevier, 2006)
This is a preprint of an article submitted for consideration in ICES Journal of Marine Research, Copyright 2006, Elsevier. ICES Journal of Marine Research is available at http://www.sciencedirect.com/science/journal/01657836 Experiments are described to investigate the survival of gadoid sh in the Barents Sea escaping from a demersal trawl, with and without a sorting grid, at high and low levels of shing intensity. The mortality for cod (Gadus morhua) and saithe (Pollachius virens) was negligible and unrelated to the experimental parameters: selection device (codend meshes and sorting grid) or shing intensity. Haddock (Melanogrammus aegle nus ) mortality was generally higher, more variable and inversely related to sh length, and was neither related to selection device nor shing intensity. The mortality of haddock escaping through the selective devices in the trawl was not signi cantly di erent from that of the control group, which avoided passing through either the codend meshes or selection grid, suggesting that the escape per se is not the main cause of mortality. It is concluded that the observed mortality of haddock is confounded by methodological problems, in particular instability of the observation cages, and does not re ect the true escape mortality.